Health Belief Model untuk Menigkatkan Kesadaran Mengikuti Vaksinasi Covid-19 dan Patuh Protokol Kesehatan di Dusun Popoh Desa Besole Tulungagung - Rio Ady Erwansyah; S. Suciati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Public awareness to take part in the Covid-19 vaccination is still lacking, due to a lack of public awareness and a lot of misinformation received by the public from various media. Therefore, it is necessary to provide the right insight to the community by using an effective educational model. The purpose of this community service is to provide education to the public directly about the definition of vaccines, their effects, the causes of post-vaccination effects, and the benefits of vaccines. This community service is intended for residents of Dusun Popoh, Besole Village, Tulungagung Regency which demographically is a southern coastal area. Activities are carried out by visiting residents to their homes and to the port where fishing boats rest. The target of education with the Health Believe Model approach is a total of 24 families living around the coast. The stages applied in the implementation of this service are divided into preparation, implementation and evaluation. The method of data collection is done qualitatively with a phenomenological approach. People who have received education said they understood the purpose and benefits of vaccination, they also said that this hands-on education made them understand about true and false news about vaccination. This educational activity is able to open the public's insight about vaccines, so that with this change in perception, it is hoped that later it will be able to increase the number of vaccination achievements.